Macro and Microanatomical Structures of Lizard’s Regenerate Tail (Mabouya multifasciata Kuhl, 1820) - Ardiana, Ardiana; Luthfi, Muhammad Ja’far; Soesilo, Nyoman Puniawati; Nisa, Laila Ainun; Widyaningsih, Risti (Proceeding International Conference on Science and Engineering, 2019)
Lizards are animals that can do autotomy. Research on the autotomy of lizard’s tail has been carried out, but few have examined about axial skeletons that focus on vertebrae caudales or arranged muscles. That is the background of this research. This research is expected to be a database for further research and as a comparison between animals that can perform other autotomies. This research intend to determine the macro and micro structures of the anatomical axial skeleton lizard’s regenerate tail and to know the micro structures of anatomy muscular segmentation lizard’s regenerate tail. The used methods are X-Ray, Alizarin Red S and Alcian Blue, Paraffin method with Hematoxylin-Eosin and Mallory Triple Strain staining. The result showed that the lizard's regenerate tail was darker than the original. On observations using X-Ray and Alizarin staining showed that the original tail is seen broad and have a Processus. The original lizard's tail is composed of bones, because it is red which shows perfectly calcified bones. While the regenerate of the lizard's tail is composed of bones in the form of long pipes which are red-colored because they have calcified from outside. Muscular segmentation of the original lizard's tail when viewed transversely has irregular segments. While the lizard's regenerate tail has 15 muscle segments. Muscles are composed of a collection of myotubes that become myotomes, each of myotomes confined by the myoseptum.